Immune deposits in skin vessels of patients with acute hemorrhagic edema of young children: A systematic literature review. Issue 1 (22nd November 2019) - Pellanda, Giorgia; Lava, Sebastiano A. G.; Milani, Gregorio P.; Bianchetti, Mario G.; Ferrarini, Alessandra; Vanoni, Federica
Abstract: Background: Acute hemorrhagic edema of young children is a benign skin‐limited vasculitis mainly affecting children 2 to 24 months of age, which is often considered the infantile variant of immunoglobulin A vasculitis (Henoch‐Schönlein purpura). In most cases, the diagnosis is made on a clinical basis without a skin biopsy. Methods: A systematic review of the literature was performed to examine the reported prevalence of vascular immune deposits in skin biopsies of patients with acute hemorrhagic edema of young children. Results: Testing for vascular immune deposits was performed in 75 cases (64 boys and 11 girls aged from 3.5 to 72, median 11 months) published between 1970 and 2018. Vessel wall deposition of complement C3 was seen in 40 cases. Immunoglobulin M (N = 24), immunoglobulin A (N = 21), immunoglobulin G (N = 13), and immunoglobulin E (N = 3) were less frequently detected. Gender, age, clinical features, and disease duration were not statistically different in cases with and without vessel wall deposition of immunoglobulin A. Conclusion: Immune deposits in skin vessels, most frequently complement C3, are common in subjects with acute hemorrhagic edema of young children, providing furhter evidence that acute hemorrhagic edema, immunoglobulin A vasculitis, and pauci‐immune vasculitides are different entities.